Charge deposition model for investigating SE-microdose effect in trench power MOSFETs. (May 2015) - Wan, Xin; Zhou, Weisong; Liu, Daoguang; Bo, Hanliang; Xu, Jun
Abstract It was demonstrated that heavy ions can induce large current—voltage (I–V) characteristics shift in commercial trench power MOSFETs, named single event microdose effect (SE-microdose effect). A model is presented to describe this effect. This model calculates the charge deposition by a single heavy ion hitting oxide and the subsequent charge transport under an electric field. Holes deposited at the SiO2/Si interface by a Xe ion are calculated by using this model. The calculated results were then used in Sentaurus TCAD software to simulate a trench power MOSFET's I–V curve shift after a Xe ion has hit it. The simulation results are consistent with the related experiment's data. In the end, several factors which affect the SE-microdose effect in trench power MOSFETs are investigated by using this model.